Food diamonds? An evaluation of the impact of alluvial diamond mining activities on the agricultural potential of land - Pienaar, Marine (My University, 2018)
South Africa depends on rainfed agriculture for a large volume of food produced and producers have to cope with erratic rainfall conditions that often result in crippling droughts. The situation is aggravated by the limited availability of soil with high crop yield potential that is further decreased by competing land uses such as urban development and mining. The study aimed to evaluate the impact that alluvial diamond mining activities have on rainfed maize production in North-West Province. Case study methodology was used to investigate the phenomenon of alluvial diamond mining and prospecting as a temporary land use on productive farmland. Soil classification data of four crop fields were analysed to determine the key soil properties that are important for sustainable crop yield in the study area. Environmental management plans submitted to the Department of Mineral Resources (DMR) as part of the alluvial diamond mining authorisation process were evaluated to determine whether these pre-mining soil properties are reflected in the process. A comparative analysis was then conducted between the soil assessment and approaches of crop producers and alluvial diamond miners on the same land. The success or failure of current rehabilitation processes to restore the agricultural potential of the land was evaluated through comparative analysis of maize yields on undisturbed and mined land over a period of six years and under fluctuating rainfall conditions. Results showed that the presence of slowly permeating subsurface soil horizons contribute significantly to high crop yield in the study area, especially during lower rainfall years. The depth and thickness of such horizons are crucial to the functionality of the higher yielding soils. In contrast to this, documents submitted as part of the environmental authorisation process, provide very limited information about the soil properties of the areas to be mined. Soil information was found to be replicated for applications over large areas without any specific soil management measures to address the heterogeneity. These documents also fail to communicate the crop yield potential of the pre-mined areas to the DMR. The comparison of yields on rehabilitated mine soil with that of undisturbed land, showed that yield losses are still suffered, even in the case of best practice soil iii rehabilitation. These differences are particularly evident in low rainfall years following high rainfall years, where stored soil-water in undisturbed soil profiles contribute significantly to the yield potential of soil. Comparative analysis between undisturbed and rehabilitated soil profiles showed that the organisation of soil horizons cannot be recreated with the rehabilitation process even when the topsoil is removed and stored separately from the overburden. Loss of the horizon organisation negatively affects the water-holding capacity of soil in the study area, thereby impacting negatively on the long-term sustainability of rainfed agriculture in this area.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Environmental Science,
Keywords: Diamond mines and mining--South Africa; Diamond deposits--South Africa